2016
DOI: 10.1590/1414-431x20165261
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous mutation in the solute carrier family 12 member 3 gene in a Chinese family with Gitelman syndrome

Abstract: Loss of function of mutated solute carrier family 12 member 3 (SLC12A3) gene is the most frequent etiology for Gitelman syndrome (GS), which is mainly manifested by hypokalemia, hypomagnesemia and hypocalciuria. We report the genetic characteristics of one suspicious Chinese GS pedigree by gene sequencing. Complete sequencing analysis of the SLC12A3 gene revealed that both the proband and his elder sister had a novel homozygous SLC12A3 mutation: c.2099T>C and p.Leu700Pro. Moreover, the SLC12A3 genes of his mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, the severity of GS is closely related to gender differences. Previous studies indicated that female GS patients had milder clinical symptoms than male GS patients even if the mutations were identical [ 12 , 13 ]. This feature was also observed in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the severity of GS is closely related to gender differences. Previous studies indicated that female GS patients had milder clinical symptoms than male GS patients even if the mutations were identical [ 12 , 13 ]. This feature was also observed in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the Gitelman syndrome, many other clinical features like hyperthyroidism and primary hyperaldosteronism may also occur with hypokalemia and episodic muscular weakness (Zhang et al, 2016). Hyperthyroidism leads to muscular weakness which is associated with electrolyte disturbances and shows signs of throtoxicosis, whereas the muscular weakness of hyperthyroidism would also lead to hypertension, hypokalemia and increased aldosterone levels (Oguz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%